What maternal health-related research matters to women in the first year postpartum? - Daly, Deirdre (My University, 2019)
﻿Background to the Maternal health And Maternal Morbidity in Ireland (MAMMI) study.
Normal Labour and Birth: 14th Research Conference
PRESENTED
Grange-over-Sands, UK
Keywords: Maternal Health; Postpartum; Maternal morbidity; Inclusive Society; Patient and Public Involvement in Research; Public Engagement in Science; Public and patient participation in healthcare; Public involvement in research; maternity care research